Miasto i myślenie projektowe. Design thinking jako skrzynka narzędziowa - Skowrońska, Marta (Człowiek i Społeczeństwo, 2019)
The paper discusses design thinking methodology, arguing that this perspective may be useful for sociology, particularly urban sociology. The author demonstrates that design thinking tools are similar to some sociological research tools. Marta Skowrońska, Miasto i myślenie projektowe. Design thinking jako skrzynka narzędziowa [Design thinking as a tool box] edited by M. Nowak, „Człowiek i Społeczeństwo” vol. XLVIII: Kuchnia badań miejskich. Studia na temat praktyki empirycznej badaczy miasta [A backstage of urban research. Studies on the empirical practices of city research scientists], Poznań 2019, pp. 75–90, Adam Mickiewicz University. ISSN 0239-3271. Marta Skowrońska, Uniwersytet im. Adama Mickiewicza w Poznaniu, Wydział Socjologii, ul. Szamarzewskiego 89, 60-568 Poznań, skowronska.marta@gmail.com